Male-sterile induction method in foxtail millet (Setaria italica) - Rizki Bagus Nugroho; WILLY BAYUARDI SUWARNO; NURUL KHUMAIDA; SINTHO WAHYUNING ARDIE (Society for Indonesian Biodiversity, 2020)
Abstract. Nugroho RB, Suwarno WB, Khumaida N, Ardie SW. 2020. Male-sterile induction method in foxtail millet (Setaria italica). Biodiversitas 21: 4325-4330. Male-sterile induction is one technique that can be used to prevent selfing in self-pollination plants, especially for plants with small floret. This study aimed to identify an effective male-sterile induction method that can kill pollen while keeping the stigma receptive in foxtail millet (Setaria italica L. Beauv). The experiment was conducted in a greenhouse at the Cikabayan Experimental Station and the Biology and Biophysics Seed laboratory, Dept. of Agronomy and Horticulture, IPB University, Indonesia from October 2018 to February 2019. The experiment consisted of two sub-experiments that were carried out with a split-plot design with four replications. The male-sterile induction method was the main plot, and the genotype was the subplot. The results from the first experiment showed that alcohol, warm water, and maleic hydrazide treatments were effective for killing pollen in the upper panicle and pollination zones. These treatments were also effective in developing unproductive rachis with different effect patterns on panicles. The results from the second experiment showed that warm water treatment and maleic hydrazide could keep the stigma receptive. From both experiments, warm water treatment was recommended for male-sterile induction in foxtail millet because it was effective in killing pollen, inflicting unproductive rachis in the upper panicle and pollination zones, and kept the stigma receptive.